Urban Food Systems Governance : Current Context and Future Opportunities - Tefft, James (FAO and the World Bank, 2021)
Ensuring adequate food for people is one of the most fundamental responsibilities of national governments. Historically, governments have invested considerable resources in increasing production of staple foodstuffs to meet national food demands with a focus on the rural farmer. However, the way we live today reveals how the food system affects nutrition and health, livelihoods and jobs and the sustainability of the planet. Changing diets, technology, urbanization, and climate change are shifting how national governments address the food system. Pandemics like Coronavirus (COVID-19) are forcing nations to face food system issues in all their dimensions. This report presents insights and emerging lessons on food systems governance from the experience of nine cities that have developed urban food interventions.